Multichannel Charge Transfer and Mechanistic Insight in Metal Decorated 2D–2D Bi2WO6–TiO2 Cascade with Enhanced Photocatalytic Performance. Issue 48 (17th October 2017) - Yuan, Lan; Weng, Bo; Colmenares, Juan Carlos; Sun, Yugang; Xu, Yi‐Jun
Abstract: Promising semiconductor‐based photocatalysis toward achieving efficient solar‐to‐chemical energy conversion is an ideal strategy in response to the growing worldwide energy crisis, which however is often practically limited by the insufficient photoinduced charge‐carrier separation. Here, a rational cascade engineering of Au nanoparticles (NPs) decorated 2D/2D Bi2 WO6 –TiO2 (B–T) binanosheets to foster the photocatalytic efficiency through the manipulated flow of multichannel‐enhanced charge‐carrier separation and transfer is reported. Mechanistic characterizations and control experiments, in combination with comparative studies over plasmonic Au/Ag NPs and nonplasmonic Pt NPs decorated 2D/2D B–T composites, together demonstrate the cooperative synergy effect of multiple charge‐carrier transfer channels in such binanosheets‐based ternary composites, including Z‐scheme charge transfer, "electron sink, " and surface plasmon resonance effect, which integratively leads to the boosted photocatalytic performance. Abstract : A rational cascade engineering of Au nanoparticles decorated 2D/2D Bi2 WO6 –TiO2 binanosheets with improved photoactivity toward reduction of nitroaromatics in water under UV–vis light illumination is reported, which benefits from the cooperative synergy effect of multiple charge‐carrier transfer channels, including Z‐scheme charge transfer, "electron sink, " and the surface plasmon resonance effect within the as‐designed ternary composite ensemble.